Sistem Pemilah Sampah Otomatis Berdasarkan Jenis Sampah Berbasis Microcontroller Arduino Uno - Firnanda, Rony; Laksono, Bagus Yudit; Masfufiah, Ilmiatul; Anam, Choirul; Firmansyah, Riza Agung; Muharom, Syahri; Septyan, Mamat (Prosiding Seminar Nasional Teknik Elektro, Sistem Informasi, dan Teknik Informatika (SNESTIK), 2024)
The waste problem is a major concern, particularly in urban areas worldwide, including Indonesia. To combat this, research is developing an automated waste sorting system focusing on organic, inorganic, and metal waste, utilizing ultrasonic sensors, inductive proximity sensors, and infrared sensors. Upon sensor detection, servo motors sort objects by moving to a 90° position, controlled by an Arduino Uno microcontroller. Test results show the device effectively sorts waste, with ultrasonic, inductive proximity, and infrared sensors able to differentiate between waste types. Metal waste achieves a success rate of 93.3%, organic waste 77.45%, and non-organic waste 93.3%, limited by sensor detection range. Research also examines mixed waste, with an average success rate of 85.9%.